Parameter optimization of debinding injection moulded Ti-6Al-4V mix with palm stearin and polyethylene - Jamaludin, M. I.; Mohamad Nor, N. H.; A. Kasim, N. A.; Saedon, J. B.; Muhamad, N. (2014)
Debinding process of injection moulded Ti-6Al-4V feedstock was divided into two parts: solvent debinding process to eliminate palm stearin (PS) and thermal pyrolysis to eliminate polyethylene (PE). Solvent debinding process used heptane at optimum temperature, 60°C to remove PS binder completely as temperature is the only parameter that can be optimized. Thermal pyrolysis parameters for removal of PE binder from the injected 65vol% Ti-6Al-4V feedstock have been optimized by using Taguchi method. Heating rate, temperature and time were the selected factors during experiment to be applied in the L9(34) Taguchi orthogonal array (OA) to find the best set of parameters to produce highest density of brown part. Thermal pyrolysis process was done at optimum parameters: heating rate: 5°C/min; temperature: 510°C; and time: 90 minutes. Analysis of Variance (ANOVA) was employed to find the best signal to noise ratio (S/N) to express the contribution of the factors towards quality characteristic. Based on the results, heating rate has the greatest contribution (54.63%), followed by duration time of thermal pyrolysis (24.40%) and temperature (19.25%).